Preparation of proton exchange membrane by radiation-induced grafting method : Grafting of styrene onto poly(ethylene tetrafluoroethylene) copolymer films - Rohani, R.; Nasef, Mohamed Mahmoud; Saidi, H.; Dahlan, K. M. (2004)
Radiation induced grafting of styrene onto poly(ethylene-tetrafluoroethylene) (ETFE) copolymer film was carried out to prepare graft copolymer (ETFE-g-polystyrene) that can host sulfonic acid groups and form proton exchange membrane for polymer electrolyte fuel cell (PEFC). The effect of monomer concentration and type of solvent on the degree of grafting was investigated. The formation of graft copolymer film was confirmed by FTIR spectrum analysis.